Beyond Being Timid, Witty, and Cynical: Big Five Personality Characteristics of Gelotophobes, Gelotophiles, and Katagelasticists. Issue 1 (2013) - Ruch, Willibald; Harzer, Claudia; Proyer, René T.
No abstract available